Chemical Composition and Cytotoxic Activity of the Essential Oils from Orobanche cernua Loefling Whole Plant. Issue 6 (2nd November 2019) - Qu, Zheng-yi; Jin, Yin-ping; Cui, Li-li; Li, Ya-li; Ren, Yan; Wang, He-cheng; Wang, Ying-ping
Abstract: Orobanche cernua is one of the species of Orobanche in Orobanchaceae family, which has been used in folk medicines for boost immunity and relieve swelling. The present study aimed to analyse the chemical constituents of the essential oils (EO) from O. cernua by GC/MS and evaluate the cytotoxic activity in vitro . Twenty-eight compounds, representing 83.41 % of the total EO were identified and the major volatile components were diethylhexyl adipate (35.34 %), followed by 2-methylheptane (12.65 %), α-cadinol (7.25 %), diethylphthalate (5.17 %), dibutyl phthalate (4.07 %), 3-methylheptane (3.51 %) and 1-tetradecanol (3.39 %). The EO cytotoxicity on the tumor cell lines (SH-SY5Y and BV-2) was determined by MTT assay and cell imaging, the results indicated that the potent cytotoxic effects with the IC50 values (55.89 μg/mL) in SH-SY5Y cells but weak in BV-2 cells with the IC50 (482.1 μg/mL) for 24 h, respectively. This paper is the first report of the chemical composition and cytotoxic activity of EO from O. cernua .